2020
DOI: 10.1055/a-1070-9132
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted versus enteroscopy-assisted endoscopic retrograde cholangiopancreatography (ERCP) in Roux-en-Y gastric bypass: a meta-analysis

Abstract: Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is technically challenging in patients with Roux-en-Y gastric bypass (RYGB) anatomy, which is increasing in frequency given the rise of obesity. Laparoscopy-assisted ERCP (LA-ERCP) and enteroscopy-assisted ERCP (EA-ERCP) are distinct approaches with their respective strengths and weaknesses. We conducted a meta-analysis comparing the procedural time, rates of success and adverse events of each method. Patients and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
(35 reference statements)
2
21
0
4
Order By: Relevance
“…The main complications of infection and bleeding are attributed to the laparoscopic portion of the procedure. Direct ERCP related complications appeared similar between LAP-ERCP and BE-ERCP (13,16). The most common ERCP related complication is pancreatitis, which is not a risk where the ampulla is not identified and therefore cannulation not attempted (a scenario more commonly seen for BE-ERCP).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The main complications of infection and bleeding are attributed to the laparoscopic portion of the procedure. Direct ERCP related complications appeared similar between LAP-ERCP and BE-ERCP (13,16). The most common ERCP related complication is pancreatitis, which is not a risk where the ampulla is not identified and therefore cannulation not attempted (a scenario more commonly seen for BE-ERCP).…”
Section: Discussionmentioning
confidence: 82%
“…In separate meta-analyses De Ponte Neto (2018) showed a native cannulation rate of 95.7% vs 82.2% for LAP-ERCP vs DBE-ERCP and 95.7% vs 62.2% compared to SBE-ERCP (15). Ayoub (2020) demonstrated a pooled cannulation rate of 97.8% vs 73.0% for LAP-ERCP vs BE-ERCP (16). The LAP-ERCP complication rate was approximately 11% and 12% higher in de Ponte-Neto's and Ayoub's analysis respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Bukhari et al [ 15 ] concluded that EDGE is superior to B-ERCP in terms of technical success and shorter procedural time. Ayoub et al [ 16 ] compared laparoscopic assisted ERCP and B-ERCP, underlining the superior effectiveness of the former, considering it as a first-line approach, even though it is associated with longer procedural time and a higher risk of adverse events. Another point to consider, besides effectiveness, is the feasibility of these procedures in all hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of therapeutic interventions via the enteroscopic route is usually limited. [1][2][3] Direct cholangioscopy has emerged as a cornerstone in the evaluation of indeterminate biliary strictures and in the treatment approach for complex biliary stones. [4][5][6] Currently, no cholangioscopy system on the market can be used via the enteroscopic approach.…”
mentioning
confidence: 99%
“…However, the efficacy of therapeutic interventions via the enteroscopic route is usually limited. 1 , 2 , 3 …”
mentioning
confidence: 99%